Crude Oil Logistics, Production and Refining in Northern Europe - Klepikov, Vladimir Pavlovich; Klepikov, Vladimir Vladimirovich (International Journal of Energy Economics and Policy, 2018)
To develop the programs to supply crude oil to North European refineries, it is necessary to take into account refineries’ location, oil refining capabilities and transportation infrastructure capacity. The paper envisages the geographic allocation of refineries and contains the evaluation of refineries’ capacities. Sustainable operations of the refineries are determined by transportation system. The assessment of capacity of crude oil transportation to the refineries is conducted. Change in the refineries’ capacities and the utilization of the refineries’ in the Northern European region was studied. Research is performed for the period of 2005/2015. The study yielded the trend towards increase in crude oil output and refining in the region. If this trend persists, the cargo flow of imported crude oil and the utilization of logistics infrastructure may increase. According to the study, the existing transport and refining infrastructure in the region is able to handle the increasing imported crude oil flow. Keywords: Oil Logistics, Oil Production, Oil Refining. JEL Classifications: F23, L71, L95, O52, R12